The Analysis of Students' Concept Mastery Levels on Hydrostatic Pressure at SMAN VII Mataram: an Introduction Study - Busyairi, Ahmad; Ayub, Syahrial (Department of Physics Education, Universitas Mataram, 2023)
Prior knowledge is one of the important factors that can affect the effectiveness of absorbing new information or concepts that students will learn. This research aims to know the mastery profile of students' concepts (prior knowledge) on hydrostatic pressure material. Descriptive research is applied in this study to realize these goals. This research was conducted at SMAN VII Mataram with a total sample of 44 students spread over four classes. Samples were taken using a simple random sampling technique. The data collection tool in this study was a concept mastery test instrument consisting of 14 questions. This test instrument measures students' mastery of concepts from cognitive level C1 (remembering) to cognitive level C4 (analyzing). Data on test results were analyzed by calculating the average percentage of students who could answer questions correctly according to the cognitive level being tested. This percentage is used as an indicator to measure the student's mastery of concepts on hydrostatic pressure material. Based on the results of data analysis, it was found that the level of student's mastery of concepts for cognitive level C1 (remembering) was 70.45%, cognitive level C2 (understanding) was 31.36%, cognitive level C3 (applying) was 27.73%, and cognitive level C4 (analyzing) was 18.94%. It can be concluded that students' mastery of concepts, especially at cognitive levels C2-C4, is still very low.